HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN HIPERTENSI PADA WANITA USIA SUBUR DI RS HJ BUNDA HALIMAH TAHUN 2024 - Erika Kusumawardani; Isramilda; Abdi Noto Pintara (Universitas Batam, 2026)
ABSTRACT Background: Hypertension is a non-communicable disease with a high prevalence among women of reproductive age, particularly those using hormonal contraceptives. The use of hormonal contraceptives is suspected to be associated with increased blood pressure through activation of the Renin-Angiotensin-Aldosterone System (RAAS). This study aims to determine the relationship between hormonal contraceptive use and the incidence of hypertension among women of reproductive age at RS Hj. Bunda Halimah. Methods: This study employed an observational analytic design with a retrospective cross-sectional approach. The sample consisted of 323 women of reproductive age at Hj Bunda Halimah Hospital in 2024, selected using the Slovin formula. Data were collected through questionnaires and blood pressure measurements, and subsequently analyzed using the Chi-square test (p < 0.05). Results: The analysis results showed that most hormonal contraceptive users experienced hypertension (88.2%), whereas most non-hormonal contraceptive users did not experience hypertension (85.7%). Statistical analysis indicated a significant association between hormonal contraceptive use and the incidence of hypertension among women of reproductive age (p = 0.001). Conclusion: There was a statistically significant association between hormonal contraceptive use and the incidence of hypertension among women of reproductive age at Hj Bunda Halimah Hospital in 2024. Keywords : Hormonal Contraceptives, Hypertension, Women of reproductive age